Lifestyle and incidence of hypertension in elderly with obesity - Yoga Tri Wijayanti; Cipto Susilo (Edukasi Ilmiah Indonesia, 2025)
Introduction: Hypertension is one of the main health problems that often occurs in the elderly, especially those who are obese. An unhealthy lifestyle, such as poor diet, lack of physical activity, and smoking habits, can worsen this condition. This study aims to analyze the relationship between lifestyle and the incidence of hypertension in the elderly and obesity, as well as identify the most influential lifestyle factors. Materials and Methods: This study used a cross-sectional design involving 200 randomly selected obese elderly respondents. Data was collected through a structured questionnaire that included information about diet, physical activity, and smoking habits. Blood pressure measurements are taken to determine hypertension status. Statistical analysis was performed using logistic regression. Results: The results of the analysis showed that a diet high in salt and low in fiber, as well as lack of physical activity, was significantly associated with an increased risk of hypertension in obese elderly (p < 0.05). Smoking habits have also been found to be a risk factor that worsens the condition of hypertension. Older people who adopt a healthy lifestyle have a lower risk of developing hypertension. Conclusions: Lifestyle modifications, including increased physical activity and dietary improvements, are important strategies in the prevention and management of hypertension in obese older adults. These findings emphasize the need for health intervention programs that focus on lifestyle changes to improve the quality of life of the elderly. This research provides a basis for the development of more effective health policies in dealing with hypertension in the elderly population